(untitled) (London Journal of Medical and Health Research, 2024)
Background: Chronic kidney disease (CKD) is a global health concern, affecting 2% of patients who may progress to end-stage renal disease (ESRD). Hemodialysis (HD) is the primary therapy, but it poses challenges, impacting patients’ quality of life. In Bolivia, CKD prevalence is 40%, making it the fourth leading cause of death. Risk factors encompass restricted access to safe water, sanitation, and exposure to toxic chemicals, presenting notable public health challenges in Bolivia.. The aim of the study is to assess Health-Related Quality of Life (HRQOL) in Bolivian HD patients through the application and validation of the cross-culturally adapted Latin-Spanish version of the KDQOL-36™ questionnaire. Methods: The cross-sectional study, approved by the Ethical Committee, involved 724 CKD patients undergoing HD in Bolivia’s La Paz department. The sampling technique used proportional allocation based on registered patients in 23 HD units across three cities. Inclusion criteria comprised patients over 18 with at least two months of HD, capable of responding to the questionnaire. The cross-culturally adapted KDQOL-36TM survey, administered by trained healthcare staff, was assessed using SPSS for reliability, exploratory, and confirmatory factor analysis, ensuring validity and appropriateness for Bolivian patients. Data was collected between October and December 2023. Results: The study included predominantly female participants (51.5%) with a mean age of 55.9 years and diverse educational backgrounds. HD was mainly received from the private health sector (65.7%), and the average duration was 31.4 months. Descriptive analysis of KDQOL-36™ scores showed variations across subscales, with symptoms and problems scoring highest (67.13, Min 10.42 Max 100) and the burden of kidney disease scoring lowest (24.61, Min 0 Max 100). Validity estimates, including McDonald’s Omega (0.92), as well as exploratory and confirmatory factor analyses, were conducted. Conclusions: The Latin-Spanish and cross- cultural adaptation version of the KDQOL-36™ questionnaire seems valid and reliable for assessing HRQOL in Bolivian patients with kidney disease undergoing HD. The sociocultural characteristics in the La Paz department may differ from those in other departments. Therefore, it is recommended to conduct this study in various Bolivian contexts. The utilization of this instrument is recommended for clinical research in Bolivia.